The Praetorians: An Analysis of U.S. Border Patrol Checkpoints Following Martinez-Fuerte - Jesus A. Osete (Washington University Law Review, 2016)
In the late seventies, the United States Supreme Court held in United States v. Martinez-Fuerte that the United States Customs and Border Protection (“CBP”) could constitutionally operate checkpoints within the United States for the purpose of conducting brief, routine questioning in order to verify a person’s citizenship and immigration status. The case was fueled by efforts to curtail the flow of undocumented immigrants into the United States from Mexico. Some of these undocumented immigrants came to the United States because of economic opportunities unavailable in Mexico. But throughout the thirty-eight-year history since the Court’s holding, some argue that CBP routinely ignores, misunderstands, or continuously refuses to acknowledge the fact that the checkpoints were to be solely utilized for immigration inquiries. In addition to preventing undocumented immigrants from entering the United States, checkpoints are utilized in other law enforcement functions, such as seizing illegal drugs and contraband, apprehending human traffickers, and intercepting unregistered firearms. One can hypothesize the endless law enforcement functions that checkpoints could serve outside the immigration context: perhaps apprehending inmates who break out of prison, catching notorious drug lords like “El Chapo” Guzman, or perhaps even preventing terrorist organizations like Al Qaeda and ISIS from committing gruesome acts against Americans. Thus, the checkpoints can pursue laudable objectives within the United States. This broader use of the checkpoints, however, “subverts the rationale of Martinez–Fuerte and turns a legitimate administrative search into a massive violation of the Fourth Amendment.” The underlying reasons the checkpoints are scrutinized are twofold. First, the “Martinez–Fuerte [court] approved immigration checkpoints for a very narrow purpose—detecting, and thereby deterring, illegal immigrants.” Second, individuals have become frustrated by the undermining of fundamental constitutional protections that, presumably, apply within the United States. Individuals traveling through the checkpoints consist of US citizens, lawful permanent residents, and foreign travelers. Hispanics primarily take issue with the controversial language from Martinez-Fuerte, where the Court allowed CBP to use “Mexican ancestry” to interrogate, and potentially search, certain individuals. Non-Hispanics likewise take issue with the checkpoints because the procedures have opened the floodgates to harassment and abuse. This Note proposes standards for checkpoint procedures that would strike an equilibrium between implementing effective law enforcement procedures at interior checkpoints and preserving constitutional values within the United States. This Note distinguishes CBP procedures conducted at the international border, which address compelling governmental interests in regulating foreign commerce and preserving national security, from CBP procedures not conducted at the international border that should be scrutinized much more stringently.
Keywords: Constitutional Law; Immigration Law; Immigration checkpoints; Undocumented immigrants; Border Patrol